Characteristics and Outcomes of Paroxysmal Sympathetic Hyperactivity in Anti-NMDAR Encephalitis - Chen, Zhongyun; Zhang, Yan; Wu, Xiaowen; Huang, Huijin; Chen, Weibi; Su, Yingying (Frontiers in Immunology, 2022)
Background: To explore the clinical characteristics and prognosis of autonomic dysfunction and paroxysmal sympathetic hyperactivity (PSH), and evaluate the efficacy of drugs used to suppress PSH episode in anti-NMDAR encephalitis patients. Methods: Patients who met the diagnostic criteria of anti-NMDAR encephalitis were enrolled from January 2012 to August 2018 and followed up for 2 years. PSH was diagnosed according to the PSH-Assessment Measure. The demographics data, clinical features, auxiliary tests results, treatments, and outcomes were prospective collected and analyzed. Results: A total of 132 anti-NMDAR encephalitis patients were enrolled, of which 27.3% and 9.1% experienced autonomic dysfunction and probable PSH respectively. Cardiac autonomic dysfunction was the most common subtype (77.8%). Patients with a higher incidence of ovarian teratoma, mechanical ventilation,neurological intensive care unit admission, and elevated glucose and NMDAR antibody titer in the CSF were more likely to exhibit autonomic dysfunction or PSH. Episodes of PSH can be suppressed by monotherapy in patients without prior sedative drug use with an efficacy of 90%. No significant difference was observed between the prognosis of patients with or without autonomic dysfunction, or between the PSH versus non-PSH groups after 6 months and even during long-term follow-up. However, patients with cardiac autonomic dysfunction had poor prognosis at 6 months. Conclusion: PSH is a common clinical condition in patients with anti-NMDAR encephalitis, especially in severe cases, and can be effectively managed by several drug monotherapies. Despite necessitating longer hospital stay, autonomic dysfunction or PSH do not seem to compromise the neurological recovery of patients.